Exploration of Physical Elements in The Traditional Game of Wela Maka In Wawowae Village - Natal, Yanuarius Ricardus; Dek Ngurah Laba Laksana; Yohanes Bayo ola Tapo; Johanes Andreas Soko (Universitas PGRI Palembang, 2024)
The aim of this research is to explore the physical elements in the traditional Wela Maka sport in Wawowae Village. The method used is descriptive qualitative with a naturalistic approach. The population in this study consisted of the people of Wawowae village who were also sports activists, and the sample was obtained using purposive sampling, resulting in a total sample of 4 people. non-test techniques (surveys) consisting of reviewing documents and archives (content analysis), observation and in-depth interviews (in-depth interviews) with community leaders, sports activists, the public and sports enthusiasts as well as analysis of available field documentation. The results of the implementation of this research are that the exploration of the physical elements contained in the wela maka or top game include: balance, eye and hand coordination, agility, strength and speed. By mastering these motor skills, a gasing player will easily master the series of movements in this wela maka game